A Cluster of MYB Transcription Factors Regulates Anthocyanin Biosynthesis in Carrot (Daucus carota L.) Root and Petiole - Iorizzo, Massimo; Cavagnaro, Pablo F.; Bostan, Hamed; Zhao, Yunyang; Zhang, Jianhui; Simon, Philipp W. (Frontiers in Plant Science, 2019)
Purple carrots can accumulate large quantities of anthocyanins in their roots and –in some genetic backgrounds- petioles, and therefore they represent an excellent dietary source of antioxidant phytonutrients. In a previous study, using linkage analysis in a carrot F2 mapping population segregating for root and petiole anthocyanin pigmentation, we identified a region in chromosome 3 with co-localized QTL for all anthocyanin pigments of the carrot root, whereas petiole pigmentation segregated as a single dominant gene and mapped to one of these “root pigmentation” regions conditioning anthocyanin biosynthesis. In the present study, we performed fine mapping combined with gene expression analyses (RNA-Seq and RT-qPCR) to identify candidate genes controlling anthocyanin pigmentation in the carrot root and petiole. Fine mapping was performed in four carrot populations with different genetic backgrounds and patterns of pigmentation. The regions controlling root and petiole pigmentation in chromosome 3 were delimited to 541 kb and 535 kb, respectively. Genome wide prediction of transcription factor families known to regulate the anthocyanin biosynthetic pathway coupled with orthologous and phylogenetic analyses enabled the identification of a cluster of six MYB transcription factors, denominated DcMYB6 to DcMYB11, associated with the regulation of anthocyanin biosynthesis. No anthocyanin biosynthetic genes were present in this region. Comparative transcriptome analysis indicated that upregulation of DcMYB7 was always associated with anthocyanin pigmentation in both root and petiole tissues, whereas DcMYB11 was only upregulated with pigmentation in petioles. In the petiole, the level of expression of DcMYB11 was higher than DcMYB7. DcMYB6, a gene previously suggested as a key regulator of carrot anthocyanin biosynthesis, was not consistently associated with pigmentation in either tissue. These results strongly suggest that DcMYB7 is a candidate gene for root anthocyanin pigmentation in all the genetic backgrounds included in this study. DcMYB11 is a candidate gene for petiole pigmentation in all the purple carrot sources in this study. Since DcMYB7 is co-expressed with DcMYB11 in purple petioles, the latter gene may act also as a co-regulator of anthocyanin pigmentation in the petioles. This study provides linkage-mapping and functional evidence for the candidacy of these genes for the regulation of carrot anthocyanin biosynthesis.